Podcast as a Tool to Popularize Political Science Knowledge into Non-Academic Audiences: The Case of Universities’ Podcasts in Poland - Szeląg, Oliwia (HAPSc Policy Briefs Series, 2023)
Increasing digitization means that education is forced to adapt technological solutions to the learning process. Podcasts are one of the forms that accompany education. This article is an analysis of political science podcasts in Poland, which are produced by academic units. The purpose of the article is to verify the methods of popularization, promotion, and distribution of political science podcasts. Study draws on qualitative and quantitative analysis of sources. The first allowed to discover what topics are covered by political science podcasts in Poland and how they are distributed. The quantitative analysis of sources made it possible to gain knowledge of the number of episodes of these podcasts produced. The author also posed three research questions 1) What are the political science podcasts in Poland that are produced by university units? 2) What topics do they cover? 3) How do the creators try to reach non-academic audiences? The study draws attention to good practices in producing and distributing political science podcasts to reach beyond an academic audience.